Cortex sparing laparoscopic adrenalectomy in a patient with Conn’s syndrome - Yetişir, Fahri (Ulus Cerrahi Derg, 2013)
Conn’s syndrome, an aldosterone producing adenoma, is a surgically curable cause of primary aldosteronism, classically treated by unilateral adrenalectomy. With the advent of laparoscopic surgery in the recent decade, laparoscopic adrenalectomy is currently accepted as the gold standard of treatment for Conn’s syndrome. Cortical sparing adrenalectomy is especially an ideal operation for patients with bilateral pheochromocytoma. This case report describes a successful laparoscopic adrenal cortex sparing surgery on the left side and anesthetic approach in a patient with Conn’s syndrome, who had a history of previous right surrenalectomy. Laparoscopic surgery without dividing the central adrenal vein can also be performed successfully in patients with Conn’s syndrome.